ROLE-PLAYING AS A LEVER FOR ARABIC LEARNING MOTIVATION IN JUNIOR MADRASAH: A FIVE-PHASE CLASSROOM SYNTAX - Ningrum, Silvya; Baili; Sabli, Muhammad; Mabruri; Anshori, Ayyub Al; Mubarok, Al (Irfani, 2024)
This study examined how role-playing was used to lift Arabic learning motivation among Grade VIII students at Madrasah Tsanawiyah Syafi’iyyah Darussalam, Tebo Regency, Jambi Province, Indonesia. A qualitative case study with two action-research cycles was conducted between February and May 2025 with one Arabic teacher and twenty-two Grade VIII students. Data were collected through 12 classroom observations of 80-minute lessons, semi-structured interviews and document analysis of lesson plans, dialogue scripts, and student journals. Coding followed the Miles–Huberman–Saldaña procedure; inter-rater agreement reached Cohen’s kappa of 0.84. A five-phase classroom syntax emerged: orientation and warm-up, vocabulary and dialogue modelling, group rehearsal, live performance, and feedback with reflection. Proportional time allocation across the 80-minute lesson placed group rehearsal at 28%, live performance at 26%, vocabulary and modelling at 22%, with orientation and feedback at 12% each. Five motivation indicators rose between baseline and end of Cycle 2: active participation from 54% to 82%, speaking confidence from 47% to 79%, on-task behaviour from 63% to 88%, vocabulary uptake from 58% to 84%, and class enthusiasm from 51% to 86%. Supporting factors included theme proximity to daily life and explicit teacher scaffolding, while shyness, time constraints, and ability heterogeneity continued to require differentiated handling. The five-phase syntax offers a transferable template for similar madrasah settings